SISTEMA DE GESTÃO INTEGRADA: UMA VISÃO DAS POTENCIALIDADES E DIFICULDADES ENFRENTADAS NA IMPLEMENTAÇÃO EM DUAS COMPANHIAS DE MINERAÇÃO DO ESPÍRITO SANTO - Piantavinha, Michey Alexandre (2005)
The potentialities and difficulties faced during the process of implementation of the System of Integrated Management (SGI) in mining companies of Espirito Santo State, as tool for the maintainable development are analyzed and discussed. The implementation of a System of Administration Integrated in the organizations involves the certification originating from of the norms ISO of the families 9000 and 14000, combined with OHSAS 18001, returned to the quality, to the environment and health and occupational safety, respectively. The diffusion and the evolution of the informations mechanisms are growing in a globalization world, that takes to the consumer a range of options in the moment of acquiring goods or services. The modern consumer relates prices and acting of the industries and makers of services, but they also consider the performance of the same ones in relation to the environmental degradation and spread social subjects through the concepts of maintainable development divulged by the Organization of the United Nations (UN). The present study looked for to gather concepts and several authors' visions on certifications of Quality, Atmosphere and Health and Occupational Safety and the existent mechanisms about the integration of the same ones in only one system, the System of Integrated Management (SGI), as economy form and better productivity in the organizations. He/she took place a field research among engineers, technicians and active specialists in steel industries of Espírito Santo State, in the which was looked for to identify difficulties and the advantages originating from of the integration of the administration systems in the same ones. It can be concluded that the process of Integrated Administration gathers countless advantages for the maintainable development, as well as it contributes so that the involved organizations obtain larger recognition in the world market and larger satisfaction on the part of their customers and of the employees involved in the system